Reading Desire : In Pursuit of Ernest Hemingway - Moddelmog, Debra (Book collections on Project MUSE., 1999)
Whether revered for his masculinity, condemned as an icon of machismo, or perceived as possessing complex androgynous characteristics, Ernest Hemingway is acknowledged to be one of the most important twentieth-century American novelists. For Debra A. Moddelmog, the intense debate about the nature of his identity reveals how critics' desires give shape to an author's many guises. In her provocative book, Moddelmog interrogates Hemingway's persona and work to show how our perception of the writer is influenced by society's views on knowledge, power, and sexuality. She believes that recent attempts to reinvent Hemingway as man and as artist have been circumscribed by their authors' investment in heterosexist ideology; she seeks instead to situate Hemingway's sexual identity in the interface between homosexuality and heterosexuality. Moddelmog looks at how sexual orientation, gender, race, nationality, able-bodiedness-and the intersections of these elements-contribute to the formation of desire. Ultimately, she makes a far-reaching and suggestive argument about multiculturalism and the canons of American letters, asserting that those who teach literature must be aware of the politics and ethics of the authorial constructions they promote.